Genome‐wide abnormalities in embryos: Origins and clinical consequences. (1st February 2021) - Masset, Heleen; Tšuiko, Olga; Vermeesch, Joris R.
Abstract: Ploidy or genome‐wide chromosomal anomalies such as triploidy, diploid/triploid mixoploidy, chimerism, and genome‐wide uniparental disomy are the cause of molar pregnancies, embryonic lethality, and developmental disorders. While triploidy and genome‐wide uniparental disomy can be ascribed to fertilization or meiotic errors, the mechanisms causing mixoploidy and chimerism remain shrouded in mystery. Different models have been proposed, but all remain hypothetical and controversial, are deduced from the developmental persistent genomic constitutions present in the sample studied and lack direct evidence. New single‐cell genomic methodologies, such as single‐cell genome‐wide haplotyping, provide an extended view of the constitution of normal and abnormal embryos and have further pinpointed the existence of mixoploidy in cleavage‐stage embryos. Based on those recent findings, we suggest that genome‐wide anomalies, which persist in fetuses and patients, can for a large majority be explained by a noncanonical first zygotic cleavage event, during which maternal and paternal genomes in a single zygote, segregate to different blastomeres. This process, termed heterogoneic division, provides an overarching theoretical basis for the different presentations of mixoploidy and chimerism.